2005
DOI: 10.1111/j.1526-4610.2005.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cortical Processing of Pain in Chronic Migraine

Abstract: CM seems to be characterized by a distinctive pattern of cortical elaboration of pain, with a prevalent activation of the rostral portion of the ACC: our results suggest that this may be a predisposing factor to migraine chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 23 publications
(75 reference statements)
3
50
0
1
Order By: Relevance
“…124 Compared with healthy controls and people with epi sodic migraine between attacks, the brain distribution of LEP is shifted rostrally in patients with migraine during an attack 125 and in patients with chronic migraine. 126 This anterior shift of activation contrasts with the pos terior shift of LEPs observed during capsaicin induced neuropathic pain in healthy volunteers, 127 and with the caudal displacement of cortical evoked potentials in the cingulate gyrus after intramuscular nociceptive stimulation of the trapezius muscle in patients with migraine. 128 This difference with the data on LEPs can be explained by the different methodologies used, which involved stimulation of different nociceptive afferents.…”
Section: Nociceptive Trigeminal Evoked Responsesmentioning
confidence: 92%
See 1 more Smart Citation
“…124 Compared with healthy controls and people with epi sodic migraine between attacks, the brain distribution of LEP is shifted rostrally in patients with migraine during an attack 125 and in patients with chronic migraine. 126 This anterior shift of activation contrasts with the pos terior shift of LEPs observed during capsaicin induced neuropathic pain in healthy volunteers, 127 and with the caudal displacement of cortical evoked potentials in the cingulate gyrus after intramuscular nociceptive stimulation of the trapezius muscle in patients with migraine. 128 This difference with the data on LEPs can be explained by the different methodologies used, which involved stimulation of different nociceptive afferents.…”
Section: Nociceptive Trigeminal Evoked Responsesmentioning
confidence: 92%
“…144,145 Connectivity was stronger between the periaqueductal grey and several brain areas associated with pain processing, such as the prefrontal cortex, anterior cingulate and amygdala, areas that are very similar to brain regions implicated in neurophysiological data on sequential cortical activa tion during painful stimuli. 125,126,144,146 Diffusion weighted MRI studies showed that microstructural alterations of white matter, and thus of functional connectivity, are present across the orbitofrontal cortex, insula, thala mus and dorsal midbrain. 147 These alterations might reflect maladaptive plastic changes driven by dysrupted exo genous and endogeneous multimodal task process ing.…”
Section: Prospects For Clinical Researchmentioning
confidence: 99%
“…Central sensitization could be associated with plastic changes in various cerebral areas belonging to the so-called pain matrix [39,40] that could be reflected neurophysiologically by the anatomical shifts found in the pain-activated cortical areas in the previously described LEP study of CM patients [11]. Central sensitization in the pain network is associated with abnormal neuronal excitability, causing a decrease in nociceptive thresholds, an increased responsiveness to both noxious and innocuous peripheral stimuli, and an expansion of the receptive fields of nociceptors [41].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a brain-mapping analysis of the cortical source of the most prominent LEP peak (P2), the same authors found that after supraorbital laser stimulation, CM patients were characterized by more pronounced activation of the rostral portion of the anterior cingulate cortex than episodic migraineurs and normal controls [11]. In addition, they observed that this positional shift of the P2 dipole, as expressed by its x-coordinate, was significantly correlated with headache frequency, but not with other clinical features or with greater self-evaluated depression and anxiety [11].…”
Section: Pain-related Responsesmentioning
confidence: 99%
“…Brain imaging studies demonstrate that ACC and its related cortical areas are activated by acute nociceptive stimuli (Talbot et al, 1991;Craig et al, 1996;Rainville et al, 1997;Strigo et al, 2003;Dunckley et al, 2005). ACC can be also activated during the empathy of pain, social rejection, and other psychological pain conditions (Eisenberger et al, 2003;Singer et al, 2004;de Tommaso et al, 2005). ACC has been reported to be activated in different chronic pain conditions (Apkarian et al, 2005;Zhuo, 2008Zhuo, , 2011.…”
Section: Introductionmentioning
confidence: 99%